Systematic Revision of the Rare Bromeligenous Genus Crossodactylodes Cochran 1938 (Anura: Leptodactylidae: Paratehnatobiinae) - Santos, Marcus Thadeu T. [UNESP]; Magalhaes, Rafael F.; Ferreira, Rodrico B.; Vittorazzi, Stenio E.; Dias, Iuri R.; Leite, Felipe S. F.; Lourenco, Luciana B.; Santos, Fabricio R.; Haddad, Celio F. B. [UNESP]; Garcia, Paulo C. A. (Herpetologists League, 2020)
Crossodactylodes is a poorly known genus of small-sized bromeligenous frogs, endemic to Brazil. They have a patchy distribution across the mountains of the Atlantic Forest and the campo rupestre ecosystem. To better resolve their evolutionary relationships, we performed phylogenetic analyses using a multigene DNA matrix and representative sampling within the genus. We then evaluated the evolution of phenotypical and natural history traits with the inferred phylogeny. We recovered Crossodactylodes as monophyletic, diagnosed by seven putative synapomorphies in morphological and natural history characters. Evidence supports some morphological synapomorphies as adaptations to the bromeligenous habit. We found high genetic distances among closely distributed lineages within C. bokermanni and C. izecksohni. Some of these lineages might represent undescribed cryptic species. We provide detailed accounts for each species including data on their geographic range, conservation, and natural history. All species of Crossodactylodes occur in highly threatened environments, are restricted to very small geographic ranges, and probably have limited dispersal capacity due to their small body size and dependence on bromeliads. These factors emphasize the need for habitat protection to safeguard species viability.
Keywords: Atlantic Forest; Campo rupestre; Character evolution; Endemism; Molecular phylogenetics; Taxonomic revision